Characterization of the core microflora and nutrient composition in packaged pasteurized milk products during storage - Ruixue Ding; Shanshan Yang; Lijuan Geng; Yumeng Liu; Baoping He; Liyun Liu; Xiqing Yue; Rina Wu; Junrui Wu (Food Science and Human Wellness)
Pasteurized milk contains complex microbial communities affected by sterilization and storage conditions. This complex microflora may be the possible reason that pasteurized dairy products are highly prone to spoilage. In this study, packaged pasteurized milk products collected from dairy processing factories in China were stored at 0, 4, 10, 15, and 25 ºC for 0−15 days and subjected to microbial identification using high-throughput sequencing. Accordingly, 6 phyla and 44 genera were identified as the dominant microbiota. Moreover, the changes in nutritional composition of the pasteurized milk, including in 16 free amino acids, 7 taste values, and 8 chemical constituents, were analyzed using principal component and multi-factor analyses. The Pearson correlation analysis identified Pseudomonas, Aeromonas, Paenibacillus, and Serratia genera as the core functional microbiota that significantly affects the nutritional composition of pasteurized milk. Hence, the results provide a comprehensive understanding of the safety and shelf-life of stored pasteurized milk.